The effect of low-level helium-neon laser on oral wound healing - Farimah Sardari; Farzaneh Ahrari (Wolters Kluwer Medknow Publications, 2016)
Background: The effectiveness of low power lasers on incisional wound healing, because of conflicting results of previous studies, is uncertain. Therefore, the aim of this study was to evaluate the effects of low-level helium-neon (He-Ne) laser irradiation on wound healing in rat's oral mucosa. Materials and Methods: Sixty-four standardized incisions were carried out on the buccal mucosa of 32 male Wistar divided into four groups of eight animals each. Each rat received two incisions on the opposite sides of the buccal mucosa by a steel scalpel. On the right side (test side), a He-Ne laser (632 nm) was employed on the incision for 40 s. Laser radiation was used just in 1 st day, 1 st and 2 nd day, 1 st and 3 rd day, and continuous 3 days in groups of A, B, C, and D of rats, respectively. The left side (control side) did not receive any laser. Histological processing and hematoxylin and eosin staining were done on tissue samples after 5 days. Wilcoxon and Kruskal-Wallis tests were used for statistical analysis. Results: Histological analysis showed that the tissue healing after continuous 3 days on the laser irradiated side was better than the control side, but there was no difference between the two sides in each groups (P > 0.05). Conclusion: This study showed that He-Ne laser had no beneficial effects on incisional oral wound healing particularly in 5 days after laser therapy. Future research in the field of laser effects on oral wound healing in human is recommended.